2020
DOI: 10.1038/s41598-020-67286-x
|View full text |Cite
|
Sign up to set email alerts
|

Bubbles determine the amount of alcohol in Mezcal

Abstract: Mezcal is a traditional Mexican spirit, obtained from the distillation of fermented agave juices. Its preparation has been conducted for centuries in an artisanal manner. the method used to determine the correct alcohol content is of particular interest: a stream of the liquor is poured into a small vessel to induce surface bubbles. These bubbles, known as pearls by the Mezcal artisans, remain stable for tenths of seconds only if the alcohol content is close to 50%. For higher or lower alcohol content, the bub… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 47 publications
(63 reference statements)
0
16
0
Order By: Relevance
“…The predicted trends of the lifetime being opposite for bubbles having a partially mobile interface, i.e., La 4, a maximum in the lifetime is expected at the transition, as observed experimentally by Nguyen et al (2013). In the experiments by Rage et al (2018) [5], however, no clear trend could be identified for Bo 1, meaning that the lifetime remains rather constant in this regime. We suspect that this experimental regime for Bo 1 is at the intermediate case between the extensional and the shear flow behaviors, the trend being inverted as outlined by Eq.…”
Section: Drainage With Surfactantsmentioning
confidence: 69%
See 2 more Smart Citations
“…The predicted trends of the lifetime being opposite for bubbles having a partially mobile interface, i.e., La 4, a maximum in the lifetime is expected at the transition, as observed experimentally by Nguyen et al (2013). In the experiments by Rage et al (2018) [5], however, no clear trend could be identified for Bo 1, meaning that the lifetime remains rather constant in this regime. We suspect that this experimental regime for Bo 1 is at the intermediate case between the extensional and the shear flow behaviors, the trend being inverted as outlined by Eq.…”
Section: Drainage With Surfactantsmentioning
confidence: 69%
“…Indeed, Nguyen et al (2013) concluded that this maximum materializes the transition between the main mechanisms driving the drainage of the film, from capillary to gravitational forces [11]. A recent experimental study of bubble lifetime inside Mezcal, a traditional agave based distilled beverage, also reports a peak in bubble lifetime at Bo ∼ 0.25 [5]. In the next paragraph, a scaling analysis is provided to justify the existence of a maximum in bubble lifetime at the transition between capillary drainage and gravitational drainage.…”
Section: Drainage With Surfactantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Note that D ∝ 1/η leads to < t b >∝ η 3 which makes a very strong impact of the viscosity on the bubble lifetime. In the case of Mezcal and water-ethanol mixture, Rage et al [62] show a dependence of the lifetime with alcohol concentration, with a maximum around 50% that they correlate to a maximum of viscosity. Lorenceau and Rouyer [59] have tested this scaling for water-ethanol mixture and found a relatively good agreement for the impact of ethanol concentration varying from 0 to 12% in mass on the bubble lifetime (Figure 7c).…”
Section: In Absence Of Stabilising Moleculesmentioning
confidence: 99%
“…Thus the first set of bubble appears to be "fragile" and to burst during film drainage for thickness much larger than 100 nm, whereas the second set of bubble presents a better resilience with respect to perturbations. For instance, films as thick as 20 µm have been measured at the rupture in Mezcal solutions [62].…”
Section: Bubble Lifetimementioning
confidence: 99%